Hypoglycemic effect of Irvingia gabonensis (Aubry-Lacomate Ex. Ororke), Baill in Type 2 Diabetic Long-Evans Rats - Hossain, M S; Sokeng, S; Shoeb, M; Hasan, K; Mosihuzzaman, M; Nahar, N; Ali, L; Rokeya, B (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Irvingia gabonensis (Aubry-Lacomate Ex. Ororke), Baill (African wild mango/bush mango) seeds are widely used in cooking as a sauce in Cameroon and in most parts of tropical Africa for the treatment of a number of ailments. In this study normal rat food was incorporated with I. gabonensis seed powder (10%) and oil free seed powder (5%) and their chronic effects on streptozotocin induced Type 2 diabetic rats were studied. Oral consumption of food incorporated with seed powder significantly reduced serum glucose level on the 28th day (p<0.01) which was comparable with glibenclamide treated group. Food with oil free seed powder showed 24% fall in glucose level on the 28th day. Fasting serum insulin increased significantly (p<0.001) in glibenclamide and oil free seed powder treated (p<0.008) groups. No effect was observed in the seed powder treated group. Liver glycogen content increased in the glibenclamide treated group but no significant change was observed in both powder and oil free seed powder treated groups. On the 28th day seed powder treated group significantly lowered serum TG level (p<0.033) and 48% was lowered by oil free seed powder. It is concluded that seed powder as well as oil free seed powder lowered blood glucose level in Type 2 diabetic model rats. It seems to act as an insulinomimetic and/or insulin sensitizing agent. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12482 Dhaka Univ. J. Pharm. Sci. 11(1): 19-24, 2012 (June)